China’s Social Credit System: A Challenge to Human Rights (Law, State and Telecommunications Review, 2023)
[Purpose] To examine the origin and evolution of China’s social credit system.[Methodology/Approach/Design] A doctrinal approach is employed with secondary sources.[Findings] China’s social credit system has some adverse effects on the fundamental principles of international human rights law.